Indonesia’s Power Shift: Business Strategies for Renewable Energy and Social Justice - Liana, Tri Melda Mei; Sianipar, Gloria J. M.; Sitorus, Sunday Ade; Setiawan, Heri; Sibuea, Nunti (International Journal of Energy Economics and Policy, 2024)
The purpose of this study is to determine and analyze the effect of renewable energy integration variables and business approaches on improving the ability of the Indonesian electricity sector in a sustainable manner with carbon emission mitigation variables as a moderating factor. The subjects of this study are electrical energy users who are customers of PT PLN Persero as many as 85,600,000 people, where the variables in this study are endogenous variables, namely the variable integration of renewable energy and business approaches, while the exogenous variable is the improvement of the ability of the Indonesian electricity sector in a sustainable manner, and the moderating variable is the carbon emission mitigation variable, where the results of data analysis are processed through SEM analysis through SMART PLS 3.0 software. From the results of existing research, it is concluded that partially the renewable energy integration variable and the business approach variable affect the improvement of the ability of the Indonesian electricity sector in a sustainable manner and the renewable energy integration variable affects the mitigation of carbon emissions. Simultaneously, the variable of renewable energy integration and business approach affect the variable of increasing the ability of the Indonesian electricity sector in a sustainable manner through carbon emission mitigation as a moderating variable. With the renewable energy integration process we can mitigate carbon emissions in accordance with existing standards, where declining carbon emissions will create the ability of the Indonesian electricity sector in a sustainable manner, where the utilization of the sustainability of the electricity sector’s capabilities requires a business approach that can be reached by underprivileged people so that later it can create affordable prices and make people’s purchasing power easier, and avoid community losses due to global warming and climate change.